Effective hand hygiene—wash your hands and reduce the risk. (9th January 2020) - Ridley, Neesha
Abstract : Neesha Ridley, Senior Lecturer, University of Central Lancashire, discusses the importance of hand hygiene in preventing healthcare-associated infections